New frontiers for environmental epidemiology in a changing world. (July 2017) - Tonne, Cathryn; Basagaña, Xavier; Chaix, Basile; Huynen, Maud; Hystad, Perry; Nawrot, Tim S.; Slama, Remy; Vermeulen, Roel; Weuve, Jennifer; Nieuwenhuijsen, Mark
Abstract: Background: In the next 25 years, transformative changes, in particular the rapid pace of technological development and data availability, will require environmental epidemiologists to prioritize what should (rather than could) be done to most effectively improve population health. Objectives: In this essay, we map out key driving forces that will shape environmental epidemiology in the next 25 years. We also identify how the field should adapt to best take advantage of coming opportunities and prepare for challenges. Discussion: Future environmental epidemiologists will face a world shaped by longer lifespans but also larger burdens of chronic health conditions; shifting populations by region and into urban areas; and global environmental change. Rapidly evolving technologies, particularly in sensors and OMICs, will present opportunities for the field. How should it respond? We argue, the field best adapts to a changing world by focusing on healthy aging; evidence gaps, especially in susceptible populations and low-income countries; and by developing approaches to better handle complexity and more formalized analysis. Conclusions: Environmental epidemiology informing disease prevention will continue to be valuable. However, the field must adapt to remain relevant. In particular, the field must ensure that public health importance drives research questions, while seizing the opportunities presented by new technologies. Environmental epidemiologists of the future will require different, refined skills to work effectively across disciplines, ask the right questions, and implement appropriate study designs in a data-rich world. Highlights: Field will be shaped by longer lifespans; shifting populations; urbanization; and global environmental change. Opportunities from rapidly evolving technologies, but public health importance should drive research questions. Adapt by focusing on healthy aging; evidence gaps in susceptible populations/low-income countries; and handling complexity.